DEEP LEARNING DAN PENGUATAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN PAI - Nur Arum; Badrul Muslim; Indah Citra Soleha; Muhammad Ikramul Mutiah; Syafriyanti; Rabahul Sri Nate; Sabrun Jamil (STKIP Subang, 2026)
This study aims to analyze the implementation of a deep learning approach in Islamic Religious Education and its contribution to strengthening students’ critical thinking skills. In the current era, Islamic Religious Education is required not only to focus on the mastery of religious subject matter but also to develop students’ critical thinking abilities in dealing with various life problems. One approach considered relevant to this need is deep learning, which emphasizes deep conceptual understanding, active student engagement, and the connection between learning materials and real-life situations. This study employs a library research method by reviewing scientific articles, books, and research reports related to deep learning, Islamic Religious Education, and critical thinking skills. The findings indicate that the application of deep learning strategies through problem-based learning, reflective discussions, and contextual learning can optimize students’ critical thinking skills, particularly in the aspects of analysis, evaluation, and moral reasoning grounded in Islamic values. In addition, teachers act as facilitators who design active, dialogic, and collaborative learning environments, thereby maximizing the development of critical thinking skills in Islamic Religious Education. Thus, the deep learning approach not only strengthens students’ understanding of Islamic teachings but also encourages the formation of reflective, critical, and Islamic-charactered learners in facing the challenges of an increasingly modern era.